Intravenous lactated Ringer's solution alone and in combination with NSAIDs in prevention of post-ERCP acute pancreatitis: an updated systematic review - Vincenzo Giorgio Mirante; Amedeo Lonardo; Simone Grillo; Francesca Franzoni; Romano Sassatelli (Open Exploration Publishing Inc., 2024)
Background: Post-endoscopic retrograde cholangiopancreatography acute pancreatitis (PEP) is the most common complication of endoscopic retrograde cholangiopancreatography (ERCP). Studies have shown that periprocedural administration of lactated Ringer's (LR) solution may prevent PEP by multiple mechanisms. To assess the evidence for periprocedural aggressive hydration with LR alone or in combination with non-steroidal anti-inflammatory drugs (NSAIDs) as a preventive measure for post-ERCP pancreatitis, an updated systematic review was conducted. Methods: Thirteen randomized controlled trials (RCTs) were selected, including eight trials (a total of 2,095 patients) evaluating aggressive hydration with LR alone and five RCTs (a total of 1,550 patients) evaluating LR in combination with NSAIDs. A critical analysis of the data was conducted. Results: RCTs evaluating the use of LR as monoprophylaxis showed that patients in the LR arm had a significantly reduced likelihood of developing PEP compared with standard hydration or placebo, and no lower likelihood than with indomethacin. RCTs investigating combined prophylaxis initially showed increased efficacy compared with single prophylactic strategies, but this superiority was no longer confirmed in more recently published trials involving larger numbers of patients. Discussion: Aggressive hydration with LR is an effective alternative prophylactic strategy to NSAIDs for PEP. Further studies are needed to ascertain whether prophylaxis with a combination of aggressive hydration with LR and NSAIDs is more effective than prophylaxis with NSAIDs alone.